Training on ANACIM Data and Maproom Tools Relevant to AICCRA - Hansen, James; Konte, Oumar; Trzaska, Sylwia; Ndiaye, Diabel; Whitbread, Anthony M.; Grossi, Amanda; Dhulipala, Ram; Ouédraogo, Issa (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
This report summarizes a workshop, which was held in Dakar on 10 November 2021, that introduced AICCRA-Senegal partners to Climate Maprooms, data, and other relevant tools and platforms that are available through ANACIM. Presentations covered ANACIM products and strategy for agriculture and related sectors, the ENACTS approach to strengthening national capacity to provide locally actionable climate information, and analyses of the quality of ANACIM’s gridded historical data that serve as a foundation for localized climate information products. Participants gained experience navigating and interpreting ANACIM’s existing suite of climate Maproom tools, and Next Generation seasonal forecast products that are expected to be launched for the 2022 rainfed growing season. Because the GTP includes the key national institutions that are involved in climate, agriculture and food security, the GTP portal hosted by ANACIM already has the endorsement of those institutions. Participants agreed that any online digital tools that the AICCRA project develops should be driven by demand, should build on and complement existing tools, and should be embedded in the GTP portal.